The Development of Prototype Polyclonal Antibody of Receptor Advanced Glycation of Endproducts (RAGE) - Mgs Irsan Saleh; Nita Parisa; Ziske Maritska (HM Publisher, 2018)
Abstract Background Receptor for advanced glycation endproducts (RAGE) is a transmembrane protein that belongs to the immunoglobulin superfamily. As its name implicates, it can bind to advanced glycation endproducts, the resulting product of non-enzymatic glycosylation, and it also has the ability to interact with multiple ligands having common motifs as a so-called multi-ligand receptor. The ligands include high-mobility group protein (B)1 (HMGB1), S-100 calcium-binding protein, amyloid-β-protein, Mac-1, and phosphatidylserine. Interaction between RAGE and its ligands activates various cellular processes, including inflammation, proliferation, apoptosis, autophagy, and migration. Methods The proccess of isolation protein of RAGE was initiated with extraction protein and purification of RAGE protein. After that, the immunization of Rats was be done to produce Anti-RAGE. The confirmation of Anti RAGE was be done by SDS PAGE and Immunobloting. Results The production of Anti RAGE was enough pure compared by Anti RAGE commercial. Anti RAGE was protein that have molecular weight around 35 kD. Conclusion The methods that used in this study effective to develop production of anti-RAGE. Keywords : Anti RAGE – Isolation – Production Antibody